Implementation of Good Agriculture Practices (GAP) in Coffee in Mekar Sari Farmers Group, Kemawi Village, Somagede District, Banyumas Regency - Na’imatul Bayyinah, Lafi; Hanifa, Hana; Sarjito, Agus; Widarawati, Rosi; Purwanto; Naila Khusna Syarifah, Risqa; Rahayuani Ratnaningsih, Hanim (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
Coffee is one of Indonesia's main commodities, playing an important role in supporting the national economy. However, coffee productivity, especially robusta, has declined in recent years. In Kemawi Village, Somagede Subdistrict, Banyumas Regency, the issue of low productivity and quality of robusta coffee has become a major challenge. This is due to the lack of implementation of Good Agriculture Practices (GAP) guidelines for environmentally friendly farming that produce safe and consumable products. This community service program aims to enhance the knowledge and skills of coffee farmers in the Mekar Sari Farmers Group regarding applying GAP in coffee cultivation. The program is conducted through a series of activities, including counseling sessions and field practices covering superior seeds, grafting techniques, organic fertilization, preparation of planting holes, planting, and pruning of robusta coffee branches. Applying GAP is expected to increase the productivity and quality of robusta coffee in Kemawi Village and serve as a model for other farmers' groups in the area.